Time-series analysis of the transcriptome and proteome of Escherichia coli upon glucose repression - Borirak, Orawan; Rolfe, Matthew D.; de Koning, Leo J.; Hoefsloot, Huub C.J.; Bekker, Martijn; Dekker, Henk L.; Roseboom, Winfried; Green, Jeffrey; de Koster, Chris G.; Hellingwerf, Klaas J. (Biochimica et biophysica acta, 2015)
Time-series transcript- and protein-profiles were measured upon initiation of carbon catabolite repression in Escherichia coli, in order to investigate the extent of post-transcriptional control in this prototypical response. A glucose-limited chemostat culture was used as the CCR-free reference condition. Stopping the pump and simultaneously adding a pulse of glucose, that saturated the cells for at least 1h, was used to initiate the glucose response. Samples were collected and subjected to quantitative time-series analysis of both the transcriptome (using microarray analysis) and the proteome (through a combination of 15N-metabolic labeling and mass spectrometry). Changes in the transcriptome and corresponding proteome were analyzed using statistical procedures designed specifically for time-series data. By comparison of the two sets of data, a total of 96 genes were identified that are post-transcriptionally regulated. This gene list provides candidates for future in-depth investigation of the molecular mechanisms involved in post-transcriptional regulation during carbon catabolite repression in E. coli, like the involvement of small RNAs. •Post-transcriptional regulation was analyzed in E. coli upon glucose repression.•For this, glucose limited chemostat-grown cells were pulsed with excess glucose.•Quantitative time-series analyses of proteome and transcriptome were performed.•Developed statistical procedures were applied specifically for time-series data.•We identified 96 genes that are subject to post-transcriptional regulation (p<0.05).